Mood disorders in dermatology consultations. (24th August 2018) - Dalgard, F.J.; Svensson, Å.; Gieler, U.; Tomas‐Aragones, L.; Lien, L.; Poot, F.; Jemec, G.B.E.; Misery, L.; Szabo, C.; Linder, D.; Sampogna, F.; Evers, A.W.M.; et al.
Summary: Recent research has suggested that a significant number of patients with common skin diseases across Europe are clinically depressed and anxious. However, dermatologists are trained to diagnose skin diseases but are not necessarily trained in diagnosing and treating mental health concerns that might be triggered by their patients' skin diseases. In this study, 3635 patients attending dermatology clinics in 13 European countries completed detailed questionnaires, using a scale called HADS, designed to assess depression and anxiety. Each patient was then examined by a dermatologist who recorded the skin diagnosis and also answered the following two questions: 'Do you see depressive signs in the patient?' and 'Do you see anxiety signs in the patient?'. The possible answers were 'yes' or 'no'. Comparing the results of the questionnaires completed by the patients with the responses to these two questions by the doctors, the dermatologists underestimated depression in 5.8% of the consultations and anxiety in 11.2% of the consultations. On the other hand, dermatologists overestimated depression and anxiety in 10% and 11.8% of the consultations, respectively. The authors conclude that overall the agreement between clinician and patient assessment of mood symptoms was poor, suggesting that mood symptoms are under‐recognized by dermatologists in a routine care setting. Abstract : Linked Article: Dalgard et al. Br J Dermatol 2018;179 :464–470